Mechanism of Regulating Informal Employment on Russian Labour Market - M. I. Glinskaya (Plekhanov Russian University of Economics, 2020)
In conditions of globalization, computerization of work places, use of flexible forms of employment it is necessary to design new radical solution aimed at regulating and stabilizing the situation connected with the rise in informal employment of the population. The article provides author’s mechanism of regulating informal employment on Russian labour market, which covers tools being used now and those put forward by the author: a new form of individuals’ work, i. e. state-freelance partnership and a tool of regulating social and labour relations on federal, regional and municipal levels on the basis of studying international and Russian normative and legal acts in the field of employment. The key goal of the mechanism is to involve informally employed population in work based on official conditions of employment. This mechanism is not a drastic solution for struggling informal employment, it is aimed at raising the work force interest in leaving the shadow employment. In unfavorable economic conditions connected with the corona-virus infection, reducing the number of jobs, loss of work by people this mechanism can act as a program of improving the situation on Russian labour market. State support in this period can raise loyalty to measures introduced by the government, whose aim is to regulate informal employment.